[5(x+1) +2(x-1)]/(x^2-1) = -6
5x+5 +2x-2 = -6x^2 + 6
6 x^2 + 7 x - 3 = 0
(2x+3)(3x-1) = 0
x = 1/3 or -3/2
Solve and check. ( 3 marks)
5/(x-1) + 2/(x+1)=-6
Here's my work on it:
5/(x-1)+2/(x+1)=?
5/(-3/2-1)+2/(-3/2+1)=-6
Can you show how I would have found x in this situation and also if I went wrong anywhere.
2 answers
The first thing I would do is get rid of the fractions
The LCD is (x-1)(x+1) so let's multiply each term by that ...
5(x+1) + 2(x-1) = -6(x+1)(x-1)
5x + 5 + 2x - 2 = -6x^2 + 6
6x^2 + 7x - 3 = 0
(3x - 1)(2x + 3) = 0
x = 1/3 or x = -3/2
I won't even attempt to figure out what you were trying to do in your last line.
The LCD is (x-1)(x+1) so let's multiply each term by that ...
5(x+1) + 2(x-1) = -6(x+1)(x-1)
5x + 5 + 2x - 2 = -6x^2 + 6
6x^2 + 7x - 3 = 0
(3x - 1)(2x + 3) = 0
x = 1/3 or x = -3/2
I won't even attempt to figure out what you were trying to do in your last line.